Modal analysis of a PMSG-based DC electrical power system in the more electric aircraft using eigenvalues sensitivity - Gao, Fei; Zheng, Xiancheng; Bozhko, Serhiy; Hill, Christopher Ian; Asher, Greg (Institute of Electrical and Electronics Engineers, 2015)
This paper deals with the modeling and small signal stability analysis of a DC-distribution electrical power system (EPS) sourced by a permanent magnet synchronous generator (PMSG). The topology employed here is one of the main candidates for future more-electric aircraft (MEA). A detailed mathematical model is developed and comprehensive EPS modal analysis is performed. Eigenvalue sensitivity and participation factor are utilized in order to assess the effect of machine and control parameters, as well as system operating conditions, on EPS stability. Furthermore, this paper also presents comparative analysis of system models with and without the inclusion of system cabling. This crucial analysis shows that the tendencies in stability behavior can be significantly different with and without cabling. It is therefore shown that system simplification, by removal of cabling, can deliver remarkably misleading results. Time domain simulations are carried out to support the theoretical analysis. The comprehensive analysis presented in this paper provides EPS designers with an extremely useful methodology for the selection of appropriate EPS parameters at the early design stages.